BANKRUPTCY OF FOREIGN COMPANIES IN INDONESIA: A JURIDICAL ANALYSIS OF THE JURISDICTION AND RECOGNITION OF FOREIGN BANKRUPTCY JUDGMENTS - Patar Bronson Sitinjak; Lucky Ferdiles (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
The increasing penetration of multinational enterprises into the Indonesian market poses intricate legal dilemmas, especially in cases of corporate insolvency. This investigation assesses the authority of Indonesia's Commercial Courts in adjudicating the bankruptcy proceedings of overseas firms and evaluates the acknowledgment of extraterritorial bankruptcy rulings under private international law principles. Employing a normative juridical methodology that incorporates statutory and conceptual analyses, the inquiry relies on primary legal sources such as statutes, supplemented by secondary materials including academic literature. The results reveal that Commercial Courts exercise jurisdiction over foreign debtors predicated on their conduct of business operations within Indonesia. Nonetheless, this authority is confined to territorial boundaries, rendering the recovery of assets situated overseas effectively impossible. Moreover, prevailing Indonesian legislation lacks explicit provisions for recognizing foreign bankruptcy judgments. Consequently, these rulings serve merely as supportive evidence and lack direct enforceability absent an international treaty or the doctrine of reciprocity. This legislative shortfall substantially undermines safeguards for creditors in transnational dealings, underscoring the pressing imperative for Indonesia to enact the UNCITRAL Model Law on Cross-Border Insolvency as a pivotal reform measure.